THE EFFECT OF WELDING CURRENT ON AISI 1045 STRENGTH AND CORROSION RATE - Iftika Philo Wardani; Vuri Ayu Setyowati; Suheni Suheni; Ilham Prajala Samudra (Institut Teknologi Adhi Tama Surabaya, 2020)
Shielded Metal Arc Welding (SMAW) was widely used in industry for joining AISI 1045 steel because this method was simple, in-expensive, and the device is portable. This researched aimed to analyze the effect of variations in welding current towards material strength and corrosion rate of AISI 1045. Welding current that been used as variations in this study are 100, 110, and 120 Ampere. This research was conducted using tensile test on the weld area and immersion around the weld area in NaCl solution with 0.4% concentration. From the research that conducted, it is known that increasing in welding current made the yield strength, tensile strength, and fracture strength of material also increased. This phenomenon also happened for elongation of material in weld area. With increasing the welding current then the elongation of material also increasing. Another aspect that researched in this paper is the effect of welding current toward corrosion rate of material. From the result, it was known that increasing welding current made corrosion rate of material became faster.